Changes in anterior and posterior hippocampus differentially predict item-space, item-time, and item-item memory improvement. (February 2020) - Lee, Joshua K.; Fandakova, Yana; Johnson, Elliott G.; Cohen, Neal J.; Bunge, Silvia A.; Ghetti, Simona
Abstract: Relational memory improves during middle childhood and adolescence, yet the neural correlates underlying those improvements are debated. Although memory for spatial, temporal, and other associative relations requires the hippocampus, it is not established whether within-individual changes in hippocampal structure contribute to memory improvements from middle childhood into adolescence. Here, we investigated how structural changes in hippocampal head, body, and tail subregions predict improvements in the capacity to remember item-space, item-time, and item-item relations. Memory for each relation and volumes of hippocampal subregions were assessed longitudinally in 171 participants across 3 time points ( Mage at T1 = 9.45 years; Mage at T2 = 10.86 years, Mage at T3 = 12.12 years; comprising 393 behavioral assessments and 362 structural scans). Among older children, volumetric growth in: (a) head and body predicted improvements in item-time memory, (b) head predicted improvements in item-item memory; and (c) right tail predicted improvements in item-space memory. The present research establishes that changes in hippocampal structure are related to improvements in relational memory, and that sub-regional changes in hippocampal volume differentially predict changes in different aspects of relational memory. These findings underscore a division of labor along the anterior-posterior axis of the hippocampus during child development.